Effect of Glucose Load on Attention and Seizures in Glucose Transporter Type 1 Deficiency Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Thirteen patients with glucose transporter type 1 deficiency syndrome (Glut-1 DS) had repeated measures of attention, memory, fine-motor coordination and well-being during a 5-hour oral glucose tolerance test in a study at Baylor College of Medicine, Houston, TX, and Columbia University Medical Center, New York, NY.